2021
DOI: 10.1002/asia.202001448
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Core‐Shell Nanocolloids with Various Core Sizes to Promote Light Capture for Green Fuels

Abstract: Core-shell nanocolloids with tailored physical and chemical merits hold attractive potential for energy-related applications. Herein, core-shell nanocolloids composed of zinc/copper sulfide (ZnS/CuS x) shells and silica (SiO 2) cores were fabricated by a template-engaged synthetic method. Interestingly, the sizes of SiO 2 cores can be tuned by different sulfurization time. In virtue of the light scattering and reflection on the SiO 2 surface, the efficiencies of light capture by ZnS/Cu 2 S shells were highly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The authors demonstrated that variations in core sizes and void space percentage result in strikingly different visible light absorption properties. The SiO 2 @ZnS/CuS x sample with 205 nm core size showed the highest light-harvesting capacity and, consequently, the highest photocatalytic H 2 production yield [139]. This report provides interesting insights into how core-shell (or yolk-shell) supported catalyst nanostructures can be designed to enhance light capture properties, hence the performance of photocatalysts for environmental and energy applications.…”
Section: Sio 2 -Based Inorganic Supportsmentioning
confidence: 83%
See 3 more Smart Citations
“…The authors demonstrated that variations in core sizes and void space percentage result in strikingly different visible light absorption properties. The SiO 2 @ZnS/CuS x sample with 205 nm core size showed the highest light-harvesting capacity and, consequently, the highest photocatalytic H 2 production yield [139]. This report provides interesting insights into how core-shell (or yolk-shell) supported catalyst nanostructures can be designed to enhance light capture properties, hence the performance of photocatalysts for environmental and energy applications.…”
Section: Sio 2 -Based Inorganic Supportsmentioning
confidence: 83%
“…As previously mentioned, spherical silica supports may also improve photocatalytic performance by enhancing optical absorption through multiple scattering steps in the silicaphotocatalyst interface, thus improving light confinement and utilization in the photoactive semiconducting layer. In addition to the already mentioned SiO 2 @TiO 2 system, such improved optical properties were recently demonstrated in other systems involving emerging visible light photocatalysts, such as SiO 2 @g-C 3 N 4 [137] , SiO 2 @g-C 3 N 4 /CdS [138] and SiO 2 @ZnS/CuS X [139], among others. The study by Ren et al [139] shows the optimization of light-scattering properties of silica-supported core-shell metal sulfides for enhanced photocatalytic production of H 2 (Fig.…”
Section: Sio 2 -Based Inorganic Supportsmentioning
confidence: 85%
See 2 more Smart Citations
“…Growing social demands are driving an upgrade in the electrical and electronics industry and calling for high-energy-density energy storage systems. Among the various candidates, lithium–sulfur (Li–S) batteries as one of the core battery technologies of the post-lithium-ion battery era have received widespread attention since their emergence in 1962, with strengths of high theoretical gravimetric energy density (2600 Wh/kg), abundant sulfur reserves, and low pollution to the environment. Figure shows some significant milestones for Li–S batteries. However, apart from the above advantages that could ensure their bright prospect, Li–S batteries have some drawbacks: (i) low utilization rate of sulfur, (ii) sluggish reaction kinetics, (iii) low conductivity of active sulfur (S 8 ) and discharging products (Li 2 S 2 /Li 2 S), and (iv) the shuttle effect of polysulfides. The shuttle effect is considered to be one of the most crucial reasons limiting Li–S batteries, which leads to decreased output capacity and low columbic efficiency (CE). …”
Section: Introductionmentioning
confidence: 99%